2009
DOI: 10.1017/s1368980009991790
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to increasing fruit and vegetable intakes in the older population of Northern Ireland: low levels of liking and low awareness of current recommendations

Abstract: Objective: To investigate barriers to increasing fruit and vegetable (f 1 v) intakes in a large sample of the older population of Northern Ireland (NI), in relation to current intakes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 33 publications
6
52
0
Order By: Relevance
“…A dislike for the taste or texture of vegetables is a barrier to achieving recommended vegetable intakes for many Americans (7)(8)(9). The incorporation of puréed vegetables into foods may be one way to help individuals overcome this barrier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A dislike for the taste or texture of vegetables is a barrier to achieving recommended vegetable intakes for many Americans (7)(8)(9). The incorporation of puréed vegetables into foods may be one way to help individuals overcome this barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that this strategy has multiple benefits because it reduces energy intakes (3)(4)(5) and increases vegetable intakes (6); it may be difficult, however, for some adults to implement. One barrier that prevents individuals from meeting recommendations to increase vegetable intakes is a dislike for the taste of vegetables (7)(8)(9). Puréeing vegetables and covertly adding them to foods while maintaining palatability could be an effective strategy to help individuals overcome this barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Demographic and lifestyle characteristics assessed were: gender, age, marital status, living status, region of residence, number of years of education, smoking habits, alcoholic drinking habits, dietary supplement taking habits, height and weight (used to calculate body mas index) and month of questionnaire completion. These characteristics have all previously been associated with FV consumption and dietary knowledge. The complete questionnaire is provided in Appendix S1.…”
Section: Methodsmentioning
confidence: 99%
“…At the first clinic visit a baseline questionnaire was administered with the intent of focusing participants on their motivations for this behaviour change and how they would overcome common barriers to dietary change [46] and how they would incorporate the vegetables, fruit and herb increase required into their daily dietary intake. The final study questionnaire assessed the participant’s experience of the dietary change, both positive and negative aspects, including financial costs and lifestyle changes they made.…”
Section: Methodsmentioning
confidence: 99%